Compact circularly polarized beam-switching wireless power transfer system for ambient energy harvesting applications - Chandrasekaran, Karthik T. (2021)
In this work, we propose a circularly polarized (CP) beam-switching wireless power transfer system for ambient energy harvesting applications operating at 2.4 GHz. Beam-switching is achieved using a low profile, electrically small CP antenna array with four elements and a novel miniaturized 4×4 butler matrix. The CP antenna is designed with an e-shaped slot and four antennas. The CP antenna measures 0.32 λ ₀ ×0.32 λ ₀ ×0.006 λ ₀ at 2.4 GHz. The antenna has a gain of 3 dBic and an axial ratio less than 3-dB at 2.4 GHz. A linear antenna array consisting of four elements is designed with the CP antenna element with an inter-element distance of 0.29 λ ₀. A 4×4 butler matrix with miniaturized couplers and crossovers are used to feed the four antenna array elements. Based on the input port of excitation, the main beam of the antenna array is demonstrated to be switched to four directions: −5°, 65°, −55°, and 20°. A CP rectenna is used to demonstrate the wireless power transfer capability of the combination of the butler matrix and the CP-antenna array. The rectenna consists of a Teo-shaped CP antenna and a rectifier. The open circuit voltage at the output of the rectenna is found to peak value of 30 mV at −3°, 61°, −53°, and 17°. Thus a complete system for CP wireless power transfer including the power transmission system as well as the RF energy harvesting sensor is designed and experimentally verified.